Distant sovereignty : national imperialism and the origins of British India - Sen, Sudipta (Routledge, 2002)
It is impossible to understand how the British came to be British without thinking about how Indians became Indian. To a significant extent colonizers and colonized made each other. In this broad study of British rule in India during the late 18th and early 19th centuries, Sudipta Sen takes up this dual agenda, sketching out the interrelationships between nationalism, imperialism and identity formation as they played out in both South Asia and Great Britain.